INFLUENCE OF FIRM AND MARKET CHARACTERISTICS ON EXPORT PROFIT OF AUTO COMPONENT INDUSTRY - V, Kavitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Exports contribute to the economic development of a country and provide a competitive edge for business organizations in the global market in earning foreign exchange. For the development of a nation, increasing export sales volume is important as it reduces the international trade gap and enhances employment and production and also facilitates the overall development of the country. The main objectives of the study are to find out the influence of firm characteristics and marketing characteristics on export profit in the auto component industry. The target respondents for the survey were the managers who have occupied the positions of export in-charge, export manager, or vice president of marketing. For this purpose, a structured questionnaire was issued to fill the data. The interaction was made with senior-level people who have knowledge about export operations. This survey was implemented by personal visits to auto component manufacturing firms. The total number of auto component companies operating in India is 647, with these firms being members of ACMA (Automotive Component Manufacturers Association of India). Of these companies, 146 auto component companies are located in South India, of which 119 companies are component-exporting companies and are actively involved in both export and domestic business out of which, 92 companies have responded. Linear regression was used as a statistical tool for the analysis purpose. The results found that firm age, firm’s export experience, firm’s total employees, number of innovations, number of employees deputed for export, export sales, share of outsource in export orders, number of quality certifications, number of foreign customers, and firm’s total sales have found significant influence on export profit of auto component manufacturers in South India.